Western Armenian phrases and their teaching as a means of enriching students' vocabulary - Kilerjian, Betty (History and Culture, 2025)
Phrases can appear in a sentence expressing figurative and literal meanings. Phrases with constituents expressing formative units are considered by many researchers to be the colorful side of the language.Therefore, students' language should be taught in such a way that it can lead to the development of skills. In fact, the level of mastery of phrases serves as an important indicator of target language proficiency.Teaching and learning phrases units helps to reveal the cognitive processes of the mind in creative thinking.At the same time, it contributes to the formation of other language skills: speaking, reading, etc. It can also lead to significant gains in vocabulary and stylistic awareness, which includes conscious perception and understanding of changes in the basic form and meaning of sentences, the stylistic coherence of the original text, and the creation of new meaning in the overall original text.The teaching of phrases at school has the main purpose of enriching students' vocabulary with figurative expressions, as well as introducing the history of the emergence of phrases, informing students about Armenian dialects, folklore, traditions, and myths.The article studies the role of Western Armenian phrases in the language teaching process and the modern methods of teaching them. Special attention is paid to the role of phrases as one of the indicators of language proficiency. With this work, we try to show what modern methods can be used to teach Western Armenian phrases, based on the fact that Western Armenian textbooks do not teach this topic.
Keywords: Western Armenian; phrase; phrase unit; vocabulary; language skills; creative thinking; teaching method